2013
DOI: 10.1542/peds.2013-0686
|View full text |Cite
|
Sign up to set email alerts
|

Improving Delivery Room Management for Very Preterm Infants

Abstract: BACKGROUND AND OBJECTIVES: Events in the delivery room significantly impact the outcomes of preterm infants. We developed evidence-based guidelines to prevent heat loss, reduce exposure to supplemental oxygen, and increase use of noninvasive respiratory support to improve the care and outcomes of infants with birth weight #1250 g at our institution. METHODS:The guidelines were implemented through multidisciplinary conferences, routine use of a checklist, appointment of a dedicated resuscitation nurse, and freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 35 publications
0
61
0
1
Order By: Relevance
“…30 That study did not have a nonparticipant group for comparison. A similar single-center study found a reduction in hypothermia (defined in that study as temperature ,36°) from 55% to 6%.…”
Section: Discussionmentioning
confidence: 97%
“…30 That study did not have a nonparticipant group for comparison. A similar single-center study found a reduction in hypothermia (defined in that study as temperature ,36°) from 55% to 6%.…”
Section: Discussionmentioning
confidence: 97%
“…48,55,66,[83][84][85][86][87] Eight observational studies (low-quality, downgraded for indirectness) found no association between hypothermia and IVH. 43,60,61,[88][89][90][91][92] For the important outcome of respiratory issues, there is evidence from 9 observational studies 44,48,50,67,83,[93][94][95][96] (low-quality evidence) showing an association between hypothermia and respiratory disease. One large randomized controlled trial 79 (low-quality evidence, downgraded for imprecision and risk of bias) found a reduction in pulmonary hemorrhage associated with improved admission temperature (OR, 0.57; 95% CI, 0.35-0.94).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Eight observational studies (very-low-quality evidence) have shown an improvement in respiratory outcomes after improved admission temperature maintenance. 44,49,51,63,72,84,93,95 Two of these have shown a decrease in respiratory support with improved temperature maintenance. 93,96 Two observational studies (very-low-quality evidence, downgraded for indirectness and imprecision) did not show any association.…”
Section: Consensus On Sciencementioning
confidence: 99%
See 2 more Smart Citations